Contribution of Organizational Culture and Organizational Communication To Teacher Performance In Integrated Islamic First Middle School - Buspami Arifin; Rusdinal Rusdinal; Nellitawati Nellitawati (Universitas Pahlawan Tuanku Tambusai, 2022)
Teacher performance is a determining factor to improve the quality of education, teacher performance greatly affects the achievement of educational goals, the better teacher performance, the easier it is to achieve educational goals , this study aims to see where the contribution of organizational culture and organizational communication to teacher performance is. conducted at the Integrated Islamic Junior High School (SMP IT) in West Pasaman Regency with a total of 84 teachers taken using a random stratified proportion technique, taking into account the strata of the group and gender, the research instrument used was a Likert scale mode questionnaire which had been tested for validity and reliability. The research data were analyzed using correlation and regression techniques. The results show that: 1) organizational communication contributes to teacher performance 16.9%, 2) organizational culture to teacher performance by 19.0%, 3) organizational communication and organizational culture together contribute to teacher performance by 24.9 %, therefore it is hoped that the principal and related elements will pay more attention to organizational culture and organizational communication in schools so that teacher performance will be even better later.